EXPLORING INDONESIAN EFL STUDENTS' CRITICAL READING STRATEGIES IN COMPOSING GROUP LITERATURE REVIEWS - Raina Farah Athaya; Gin Gin Gustine (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
The academic expectations for higher education EFL students demand sufficient English proficiency in academic reading. This adds the pressure of a quality learning environment that can provide comprehensive education using authentic assignments. Therefore, this study explored EFL students’ firsthand use of critical reading strategies in enacting academic reading. This study utilized a qualitative case study that involved seven EFL students enrolled in an academic reading course. The data were collected using a document analysis of the literature review section of their research proposal and semi-structured interviews. The data were analyzed using thematic analysis with a critical reading strategy framework. The findings showed EFL students applied ten critical reading strategies: Annotating, previewing, contextualizing, analyzing, outlining, summarizing, paraphrasing, synthesizing, questioning, and reflecting to overcome difficulties when enacting academic reading to compose literature reviews. These strategies were activated along with collaborative teamwork and purposeful integration of AI and digital tools. These findings offer pedagogical insights into how group collaboration and emerging digital tools can enhance EFL students’ academic reading learning experiences.